Deep water vetulicolians from the lower Cambrian of China - Shuhan Ma; Julien Kimmig; James D. Schiffbauer; Ruibo Li; Shanchi Peng; Xianfeng Yang (PeerJ)
Vetulicolians are an enigmatic phylum of extinct Cambrian marine invertebrates. They are particularly diverse in the Chengjiang Biota of China, but representatives have been recovered from other Fossil-Lagerstätten (Cambrian Stage 3-Drumian). These organisms are characterized by a bipartite body, which is split into an anterior section and a posterior segmented section connected by a narrow constriction. Here we report new material of the genus Pomatrum from the Cambrian Balang Biota (Series 2, Stage 4) of Hunan, southern China. This is the first discovery of this vetulicolian outside of the Chengjiang Biota (Series 2, Stage 3) and the first report of vetulicolians from the Balang Biota. This finding not only suggests that this group had a wider spatial and temporal distribution than previously known, but also adds information to the overall biodiversity of the Balang Biota—one of the most important Stage 4 fossil deposits known from Gondwana.